Womens Rights In Torah - Ali, Viyan S. (Humanities Journal of University of Zakho, 2016)
Judaism in the origin of religion heavenly revealed teachings of the prophet Moses –peace upon him –and distorted beyond much of what led the distortion and misrepresentation of what led to the distortion and misrepresentation of women's rights , the original Judaism woman honored as considered that a mother bear children and bring them , and considered that a good wife happiness for men and separated the sexes in temples and public life warding off to temptation and evil also denied looking at foreign women and adultery .However, the distortion in the Jewish status of women in the shrine of humiliation and shame unenviable women in Judaism distorted the cause of sin and the rabbis (scholars) in their teachings (the women and the pot is full of Balaqmar) greedy, lazy, envious, and the campus of the Talmud Daaoualmroh for her husband because she curse him, and deprived Read Mishna (the Bible) and the Torah on women and children and slaves, and prevented the women from the certificate and swearing, and is considered an adult woman without a baby in Manzala and deprived them speak with foreign men, but the husband's relatives . Jewish religion has come a long way from the degradation of women in their community took all or most of their rights